Murottal and Clasical Music Therapy Reducing Pra Cardiac Chateterization Anxiety - Sapta Darmadi; Yunie Armiyati (South East Asia Nursing Research, 2019)
The high incidence of patients with coronary heart disease is directly proportional to the increase in cardiac catheterization. Many patients who experience anxiety pre heart catheterization will need nursing action. Relaxation with classical music therapy and or murottal therapy can reduce patient anxiety.  The aim of this study was to determine the effectiveness of murottal therapy and classical music therapy to reduce the anxiety of patients pre heart catheterization in the Elang Installation of Dr. Kariadi Hospital Semarang. The study was a Quasi Experiment study with two group pre and post-test design. The research sample consisted of 16 patients in the classical music therapy group and 16 in the murottal therapy group. The results of the study showed that there were differences in the effectiveness of murottal therapy and classical music therapy to decrease the anxiety of patients pre heart catheterization in the Elang Installation of Dr. Kariadi Hospital Semarang (p-value 0.028).  Murottal therapy is more effective in reducing anxiety. Music therapy and murottal therapy given with a duration of 30 minutes create a calm and comfortable atmosphere so that the body becomes more relaxed, blood circulation more smoothly, blood pressure and other vital signs will decrease and can reduce anxiety in pre cardiac catheterization patients. Murottal therapy is more effective in reducing anxiety in pre cardiac catheterization patients.